›Die‹ Gewalt und ›wir‹ (Nomos Verlagsgesellschaft mbH & Co. KG, 2025)
How to live with unsublatable violence is to be understood in the context of a culture of sensitization to violence, whose history from war to recent disasters is discussed as well as the diversity in which violence occurs - hurtful, discriminatory, in forms of abuse, but also in the legitimization of violence. The starting point is the question of how a 'we' is assumed in the critique of violence in contrast to others who resort to all possible forms of violence. This 'we' is suspected of resulting from Western self-righteousness and reinforcing it. These social-philosophical contributions to the history, experiences and current focal points of the discussion on violence counteract this.